PROMOTING GRAMMAR AWARENESS THROUGH TASK ACTIVITIES - Muhammad Reza Alizain (Journal of Applied Linguistics (ALTICS), 2019)
ABSTRACT Despite the continuous debate regarding whether it is necessary to teach grammar explicitly or implicitly in the language classroom, the debaters could agree that grammar awareness is significant for language learners. Many methods have been conducted by language teachers or researchers to promote language learners’ grammar awareness, and one of them is through ideally designed task activities. Grammar awareness is a particular skill in language learning which can be acquired which is quite different from other language skills which deal with language productions or language comprehensions. Grammar awareness is a skill which could allow its possessor to identify the structure of a language rather than the meaning. Therefore, the activities to promote this skill should be logically different from activities to promote either production skills or comprehension skills. The purpose of this paper is to provide several alternatives, especially classroom activities, to promote grammar awareness which can be used effectively. Keywords: grammar awareness, activities, language, explicitly, implicitly